MEMBANGUN MENTALITAS CINTA MELALUI MATA KULIAH ILMU BUDAYA DASAR DENGAN NILAI-NILAI ISLAM NORMATIF - Takdir Alisyahbana (Sekolah Tinggi Agama Islam (STAI) Bumi Silampari, 2016)
Integrating normative values ​​of Islam to the basic culture of Indonesia, will provide a solid foundation for the development of each individual mentality. Because the values ​​offered by Islam is rahmatan lil Alamin. The value of love, will be more robust when the normative values ​​of Islam are integrated into it. As the love of Allah, the Prophet Muhammad, parents, ourselves, our fellow human beings and the environment. For the normative values ​​of Islam based on love relegius values ​​are in line with the nation's cultural godless Almighty.